TEACHING SPEAKING ENGLISH TO YOUNG LEARNERS:A CASE STUDY OF STUDENTS ON 4TH GRADE IN ONE OF INTERNATIONAL ELEMENTARY SCHOOL IN CIKASO KUNINGAN - Rina Yuliani, - (2010)
This study entitled "Teaching Speaking English to Young Learners", is aimed at finding out ways of teaching Speaking English and the difficulties experienced by the teacher during the process of teaching speaking English to the children at one of International Elementary School in Cikaso Kuningan. The subject of this study is the fourth grade English teacher who is teaching English in one of International Elementary School in Cikaso Kuningan. The data were collected from classroom observations and interviews. Which were analyzed by utilizing the theories of Linse and Nunan (2005). Based on the data analysis result, it shows that the teacher uses Audiolingual Method as teaching method, Choral Response and Dialogue as a technique, course books and computer-based presentation technology as media, a direct and an indirect test as assessment. However the teacher faces some problems dealing with teaching pronunciation and delivering material to the students especially for those with special needs. Therefore, it is recommended that the teacher apply various and interesting activities, children friendly media which are suitable for the young learners characteristics.